Economic evaluation of biosimilars for reimbursement purposes - what, when, how? - Evelien Moorkens; Hannah Broux; Isabelle Huys; Arnold G. Vulto; Steven Simoens (Taylor & Francis Group, 2020)
Background: Limited previous research and guidelines on the design of economic evaluation for biosimilars have led to unresolved methodological questions on how to assess biosimilars. Objectives: We want to raise awareness of and explore methodological issues for the economic evaluation of biosimilars. Methods: We relied on a literature review, exploratory interviews, and our experiences. Results and Conclusions: In the majority of cases in which reimbursement for a biosimilar is sought, it will not be necessary to conduct an economic evaluation, given that the reference product is already reimbursed and standard of care. If the latter is not the case, a full economic evaluation of the biosimilar versus standard of care is needed. This might also be needed in the case of differences in administration form or adherence (for example, due to a nocebo effect) and to take into account value-added services. The entry of biosimilars and of next-generation biological products should trigger a re-assessment of the entire product class. HTA bodies and reimbursement agencies should provide clear guidance on how to assess the value of a biosimilar in each of these circumstances.